Bitumen recovery from Buton oil sands using a surfactant under the effect of ultrasonic waves. Issue 2 (17th January 2016) - Zou, Changjun; Zhao, Pinwen; Ge, Tingting; Li, Dan; Ye, Hui; Huang, Gang
ABSTRACT: A new process for ultrasonic-assisted surfactant extraction of bitumen from Buton oil sands is performed. The microstructure and composition of Buton oil sands are characterized. The results demonstrated that its inorganic mineral contains 95.2% calcite and the particle size is mostly 2–5 μm. The extraction experiments show that the bitumen recovery ratio of nonylphenol polyoxyethylene ether (NP-12) is 91.6%. Ethylene oxide number and hydrophile-lipophile balance have significant effects on the bitumen recovery ratio. In addition, the bitumen recovery ratio of NP-12 can still reach 90.2% after being recycled five times.